Protocol for an aged cohort study to create a single indicator that expresses the trajectory of intrinsic capacity over the years and its relation to functional abilities - Simões, E. J.; Perracini, M.; Mello, M. A. F.; Cohrs, F. M.; Neumann, A. P. F. M.; Demarzo, M.; Ramos, L. R. (Frontiers in Aging, 2025)
Population aging will be on the public health agenda in the coming decades. By 2050, 16% of the world’s population will be aged 65 and above, mostly living in middle- and low-income countries. In Brazil, the aged population will triple by 2050, from less than 20 million to approximately 65 million, making it the sixth largest aged population in the world. Population aging is associated with an increase in the prevalence of chronic non-communicable diseases, which in turn promotes a functional decline in people who age. This often leads to limitations in daily life and dependence, with clear implications for the quality of life and health costs. In 2015, the World Health Organization proposed the concept of intrinsic capacity (IC) as a multidimensional health indicator that encompasses the essential physical and mental capabilities for people to perform what they need and like in daily life, regardless of the chronological age. In practice, IC was operationalized in five health domains, namely, cognitive, psychological, sensory, locomotor, and vitality. These domains, which are evaluated together and over time, offer the function parameters necessary to understand different, person-centered aging trajectories. Prevention of age-associated functional decline has not been studied well. Literature lacks studies that indicate the expected values for different IC trajectories related to aging, with or without disability. Few studies have analyzed IC as a risk factor for compromising the functional ability (FA) of the elderly, which is measured by the degree of dependence in activities of daily living, the risk of falls, and early mortality, while controlling for all known risk factors for functional decline. The cohort study proposed here, called “Longevity with Functionality (LONGFUN),” addresses the growing importance of evaluating the indicators of IC in a prospective way, creating a single indicator, and relating it to the FA of the aged population.